The The Urgency of Philosophy of Science as an Epistemological Basis for the Development of Science - Aditra Zulfi; Delfiani; Intan Putri Refita; Nadya Meisya Putri; Rike Kartika Sari; Desyandri (Journal of Practice Learning and Educational Development, 2026)
The philosophy of science plays a fundamental role in the development of science, particularly as an epistemological basis that determines how to acquire, validate, and develop scientific knowledge. This article aims to examine the urgency of the philosophy of science in building a solid epistemological foundation for the development of science amidst the dynamics of scientific and technological progress. The approach used in this research is a literature study using a descriptive-critical analysis method of various relevant literature, including books, scientific journals, and classical and contemporary philosophical works. The results of the study indicate that the philosophy of science plays a role in explaining the basic assumptions of science, the limitations of scientific knowledge, and the criteria for truth and validity of science. In addition, the philosophy of science also functions as a reflective and critical tool in addressing epistemological problems, such as objectivity, the scientific method, and the relationship between science and human values. Thus, the existence of the philosophy of science as an epistemological basis is crucial to ensure that the development of science is not only technical and pragmatic, but also rational, systematic, and philosophically responsible. This article is expected to provide a theoretical contribution in strengthening understanding of the strategic role of the philosophy of science in the sustainable development of science.